Bisphenol A single and repeated treatment increases HDAC2, leading to cholinergic neurotransmission dysfunction and SN56 cholinergic apoptotic cell death through AChE variants overexpression and NGF/TrkA/P75NTR signaling disruption - Moyano, Paula; Flores, Andrea; García, José Manuel; Anadon, María José; Frejo, María Teresa; Sola, Emma; Pelayo, Adela; del Pino, Javier; García Lobo, Jimena (My University, 2021)
Bisphenol-A (BPA), a widely used plasticizer, induces cognitive dysfunctions following single and repeated exposure. Several studies, developed in hippocampus and cortex, tried to find the mechanisms that trigger and mediate these dysfunctions, but those are still not well known. Basal forebrain cholinergic neurons (BFCN) innervate hippocampus and cortex, regulating cognitive function, and their loss or the induction of cholinergic neurotransmission dysfunction leads to cognitive disabilities. However, no studies were performed in BFCN. We treated wild type or histone deacetylase (HDAC2), P75NTR or acetylcholinesterase (AChE) silenced SN56 cholinergic cells from BF with BPA (0.001 ¿M¿100 ¿M) with or without recombinant nerve growth factor (NGF) and with or without acetylcholine (ACh) for one- and fourteen days in order to elucidate the mechanisms underlying these effects. BPA induced cholinergic neurotransmission disruption through reduction of ChAT activity, and produced apoptotic cell death, mediated partially through AChE-S overexpression and NGF/TrkA/P75NTR signaling dysfunction, independently of cholinergic neurotransmission disruption, following one- and fourteen days of treatment. BPA mediates these alterations, in part, through HDAC2 overexpression. These data are relevant since they may help to elucidate the neurotoxic mechanisms that trigger the cognitive disabilities induced by BPA exposure, providing a new therapeutic approach.
Keywords: Bisphenol A ,SN56 basal forebrain cholinergic neurons ,HDAC2, NGF ,P75NTR ,TrkA ,AChE ,ChAT